Trained lay coaches and self-care cognitive-behavioral tools improve depression outcomes. Issue 8 (August 2022) - McCusker, Jane; Lambert, Sylvie D.; Ciampi, Antonio; Jones, Jennifer M.; Li, Madeline; Yaffe, Mark J.; Pelland, Marie-Eve; Belzile, Eric; de Raad, Manon
Abstract: Objectives: Identify the key effective components of a depression self-care intervention. Methods: Secondary analysis of data from 3 studies that demonstrated effectiveness of a similar depression self-care intervention (n = 275): 2 studies among patients with chronic physical conditions and 1 among cancer survivors. The studies used similar tools, and telephone-based lay coaching. Depression remission and reduction at 6 months were assessed with either PHQ-9 (chronic condition cohorts) or CES-D (cancer survivor cohort). Multiple logistic regression was used to analyze data when the interaction p-value with cohort was < 0.10. Results: The 3 coached cohorts achieved better depression outcomes than usual care. The combination of coaching and joint use of 2 tools based on cognitive-behavioral therapy (CBT) was associated with depression remission and reduction among chronic condition cohorts but not among cancer survivors. Neither the number nor the length of coach calls were associated with outcomes in pooled data. Conclusions: Trained lay coaching and use of CBT-based self-care tools were associated with improved depression outcomes in patients with chronic conditions but not among cancer survivors. Practice implications: Trained lay coaching and CBT tools are key components of depression self-care interventions. Further research is needed on the effective components in cancer survivors. Highlights: We pooled data from 3 studies (5 cohorts) of depression self-care interventions. Cohorts receiving trained lay coaching achieved better depression outcomes. Joint use of 2 CBT self-care tools was associated with better depression outcomes. Different effects were seen in chronic physical condition cohorts vs cancer survivors.